2009
DOI: 10.1093/hmg/ddp235
|View full text |Cite
|
Sign up to set email alerts
|

Uromodulin mutations causing familial juvenile hyperuricaemic nephropathy lead to protein maturation defects and retention in the endoplasmic reticulum

Abstract: Familial juvenile hyperuricaemic nephropathy (FJHN), an autosomal dominant disorder, is caused by mutations in the UMOD gene, which encodes Uromodulin, a glycosylphosphatidylinositol-anchored protein that is expressed in the thick ascending limb of the loop of Henle and excreted in the urine. Uromodulin contains three epidermal growth factor (EGF)-like domains, a cysteine-rich region which includes a domain of eight cysteines and a zona pellucida (ZP) domain. Over 90% of UMOD mutations are missense, and 62% al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 44 publications
5
110
1
1
Order By: Relevance
“…In accordance with previous reports (4,7,9,19,21), about 80% of mutations were in exon 4. Mutations are likely to cause misfolding and structural destabilization, leading to impaired trafficking of the mutant protein, which probably plays a key role in the development of TIN (7, 21,22). Exons 4 and 5 encode a highly conserved cysteine rich sequence and three calcium-binding EGF domains (23).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous reports (4,7,9,19,21), about 80% of mutations were in exon 4. Mutations are likely to cause misfolding and structural destabilization, leading to impaired trafficking of the mutant protein, which probably plays a key role in the development of TIN (7, 21,22). Exons 4 and 5 encode a highly conserved cysteine rich sequence and three calcium-binding EGF domains (23).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these mutations are clustered in exons 4 and 5 and located in the N-terminal half of the protein [21][22][23][24][25]. The mutations cause significantly delayed maturation and trafficking of the mutant uromodulin, which in turn results in its retention in the ER, reduced expression at the plasma membrane, and decreased secretion into the tubular lumen [24,[26][27][28].…”
Section: Pathophysiologymentioning
confidence: 99%
“…It has been shown that the mutant uromodulin cannot exit the ER of TAL cells, resulting in intracellular accumulation of the mutant protein and consequent cell damage [24,26,27]. This may incite an immune response with infiltration of immune cells and pro-fibrinogenic lymphokine production in the tubulointerstitium [29].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Uromodulin is likely to contain three epidermal growth factor (EGF)-like domains; the second and third domains contain a calcium-binding motif, a domain of eight cysteine residues (D8C) within a cysteine-rich region, and a zona pellucida (ZP)-like domain, which is responsible for the polymerization of extracellular proteins into helical filaments [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that modifier genes, in addition to environmental factors, have an effect on clinical findings [5]. Moreover, Williams et al [4] reported that UMOD mutations may be classified based on the mature:precursor ratio of uromodulin. In their study, the group of patients with C32W, D196N, and G488R mutations had a higher mature:precursor ratio of uromodulin than the group with C126R, N128S, and C223R mutations.…”
Section: Discussionmentioning
confidence: 99%